Perbedaan Teknik Clapping dan Vibrating terhadap Bersihan Jalan Nafas pada Anak dengan ISPA - Joko Sutrisno; Sutrisno; Dedi Saifulah; Roslin Kono (Universitas STRADA Indonesia, 2022)
The problem often faced by children when experiencing ARI is that they cannot excrete sputum maximally, most of which is saliva.. Literature sourced from google scholar, google scholar and PubMed databases published from 2015 to 2020, and manually select articles relevant to the research question. The results were carried out on respondents from 9 reviewed journals, 7 journals were proven effective for expelling phlegm in children who experienced an ineffective airway. Respondents whose sputum did not come out was (26.7%) and sputum that did not come out was (73.3%). While in the control group, there were 5 patients (71.4%) who still had sputum. Cleansing the airway before being given clapping and vibration, it was found that 16 (100%) of the respondents had sputum, after giving clapping and vibration it was found that 13 (81.2%) respondents had no sputum. The results also found that the clapping technique was more effective in cleaning the airway. It was concluded that there were differences in clapping and vibrating techniques on airway clearance in children with ARI. The difference in clapping and vibrating techniques for clearing the airway in children with ARI is located in sputum production as sputum production can increase due to physical, chemical stimulation, or due to infection. It is hoped that the clapping and vibration action in children must be careful and slow because the strength of the bones and organs of the child is still growing. These clapping and vibrating techniques are carried out routinely for 2 times a day, in the morning to reduce secretions that accumulate at night and are done in the afternoon to reduce coughing at night.